Studi Literatur: Pengaruh Perinatal Depression dan Pola Konsumsi Ibu terhadap Kualitas ASI - Mitha Nur Azizah (Media Gizi Kesmas, 2023)
Background: Perinatal depression is a condition of psychological disorder in mothers after giving birth. Prolonged perinatal depression in mothers can cause low birth weight (LBW) and impaired social, cognitive, and emotional development in infants. Apart from the pressure of depression that must be avoided, the eating patterns of breastfeeding mothers greatly affect the quality and production of breast milk. Balanced nutrition will produce good nutrition and quality, and good breast milk nutrition will affect the baby's development. Objectives: This study aims to provide information to determine and analyze the effect of perinatal depression and maternal consumption patterns on the quality of breast milk. Methods: Search articles through PubMed and ScienceDirect databases with filtering results for eligible articles to find 10 articles. Once obtained, then an assessment of the article is carried out to the stage of making a literature review. Discussion: There were 10 articles that discuss the relationship between perinatal depression and maternal consumption patterns on breast milk quality. Conclusion: There was an influence between perinatal depression and maternal food consumption on the quality of breast milk, psychological conditions and depression experienced by the mother also affect the diet and nutrition consumed by the mother so that it will have an impact on the quality of the milk produced.